2021
DOI: 10.1016/j.ijimpeng.2020.103673
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the fluid-structure interaction during the water impact of thin aluminium plates at high horizontal speed

Abstract: The water impact of an inclined flat plate and at high horizontal velocity is experimentally investigated with focus on the fluid-structure interaction aspects. Several test conditions have been examined by varying the vertical to horizontal velocity ratio, the pitch angle and the plate thickness. Measurements are performed in terms of strains, loads and local pressure. The study highlights the significant changes in the strains and, more in general, in the structural behaviour when varying the plate stiffness… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The objective of these experiments is to provide an estimate of the forces acting on the fuselage during a guided water landing, thus to retrieve essential information on the aircraft dynamics in this critical phase. Whereas an accurate reproduction of the hydrodynamic phenomena and of the fluid-structure interaction aspects occurring in the ditching phase necessarily needs full scale tests on sample specimens [40,3,41,42], the investigation of the aircraft dynamics at ditching can be only conducted with small-scale free-flight tests [43,44,45]. The difficulties in achieving a precise control of the attitude of the aircraft when it touches the water, together with the strong non-linearity of the loading associated to the water impact, make such kind of tests not very useful neither for the verification of the final design, nor for the validation of computational model used in the design phase.…”
Section: Experimental Setup and Datamentioning
confidence: 99%
“…The objective of these experiments is to provide an estimate of the forces acting on the fuselage during a guided water landing, thus to retrieve essential information on the aircraft dynamics in this critical phase. Whereas an accurate reproduction of the hydrodynamic phenomena and of the fluid-structure interaction aspects occurring in the ditching phase necessarily needs full scale tests on sample specimens [40,3,41,42], the investigation of the aircraft dynamics at ditching can be only conducted with small-scale free-flight tests [43,44,45]. The difficulties in achieving a precise control of the attitude of the aircraft when it touches the water, together with the strong non-linearity of the loading associated to the water impact, make such kind of tests not very useful neither for the verification of the final design, nor for the validation of computational model used in the design phase.…”
Section: Experimental Setup and Datamentioning
confidence: 99%
“…In a computational study on the 2-D oblique impact of an elastic plate (beam) with free-free boundary condition at both ends on a thin liquid layer, Khabakhpasheva & Korobkin (2020) also show the possibility of air entrainment as a consequence of plate deformation and rotational motion. Spinosa & Iafrati (2021) conducted an experimental study of the water impact of aluminum plates at large horizontal speed and it is pointed out that the structural deformation causes a reduction in peak pressure and an increase in the total load. Faltinsen (1999) proposed an orthotropic plate theory for the coupled analysis of the structural dynamics and the flow motion during the vertical water entry of a ship panel.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, water entry tests on flat plate ditching at high horizontal speed were performed in Iafrati et al (2015) and in Iafrati (2016). Particular attention was also paid to the analysis of the structural deformations, see Spinosa and Iafrati (2021). The study was further extended to double curvature specimens, for which hydrodynamic phenomena such as cavitation and ventilation have been observed to be important (see Iafrati and Grizzi (2019); Iafrati et al (2020)).…”
Section: Introductionmentioning
confidence: 99%
“…These works have shown that during the impact phase a localised high pressure area develops on the submerged part of the aircraft at the spray root (Climent et al (2006); Seddon and Moatamedi (2006)). The large pressure areas result in very large hydrodynamic loads, which can lead to a possible structural damage of the fuselage and to fluid-structure interaction phenomena (Groenenboom and Cartwright (2010); Cheng et al (2011); Hughes et al (2013); Groenenboom and Siemann (2015); Spinosa and Iafrati (2021)).…”
Section: Introductionmentioning
confidence: 99%